Double-Duty Actions to Reduce the Double Burden of Malnutrition in Indonesia - Rian Diana (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: : Indonesia is facing a double burden of malnutrition (DBM). Double-duty action was promoted by WHO in 2017 which aims to tackle the double burden of malnutrition simultaneously. Objectives: This study analyzed factors associated with the double burden of malnutrition and potential of double-duty action (DDA) that is suitable for Indonesia Methods: This study is a provincial-level aggregate data set from Indonesia Basic Health Survey 2018 and National Socio-Economic Survey 2018 which covered 34 provinces. A serious DBM characterized by persistent stunting (children under five) ≥30% and coexisting overweight and obesity in adults ≥30% at the same time. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze factors associated with DBM.Results: High prevalence of stunting and overweight and obesity in almost all provinces di Indonesia. Seventeen provinces were having a serious DBM. Health care access, exclusive breastfeeding and socio-economic associated with DBM. There were 4 potential DDA for Indonesia: health care which consist of antenatal care, maternal and child care, exclusive breastfeeding, child growth monitoring, and social safety net. Conclusions: Addressing the DBM through four potential DDA can be a new paradigm, mindset, and critical importance in achieving Indonesia’s target in reducing under and over nutrition simultaneously.